2022
DOI: 10.1108/k-03-2022-0373
|View full text |Cite
|
Sign up to set email alerts
|

Impact of knowledge absorptive capacity on innovative performance in SMEs: mediating effect of cluster environment

Abstract: PurposeThis study builds on knowledge-based view (KBV) research and the natural resource-based view of the firm (NRBV) to examine the effect of knowledge absorptive capacity on innovative performance. It also investigates the mediating role of three dimensions of the cluster environment: degree of network, institutional environment and access to factors of production.Design/methodology/approachBy means of partial least squares-based structural equation modelling method, the study validated and analysed the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 131 publications
0
5
0
Order By: Relevance
“…Tese studies found that absorptive capacity is a critical determinant for nurses' creative and innovative behavior. Conversely, the studies of Maleski et al [54] and Fulgence et al [27] yielded that employees' performance including the creative abilities is not signifcantly afected by knowledge absorptive capacity. Tis contradiction with our fnding may be the presence of confounding factors like employees' traits, work environment, and motivation in the linkage between creativity and absorptive capacity.…”
Section: Organizational Absorptive Capacity and Nurses'mentioning
confidence: 92%
See 1 more Smart Citation
“…Tese studies found that absorptive capacity is a critical determinant for nurses' creative and innovative behavior. Conversely, the studies of Maleski et al [54] and Fulgence et al [27] yielded that employees' performance including the creative abilities is not signifcantly afected by knowledge absorptive capacity. Tis contradiction with our fnding may be the presence of confounding factors like employees' traits, work environment, and motivation in the linkage between creativity and absorptive capacity.…”
Section: Organizational Absorptive Capacity and Nurses'mentioning
confidence: 92%
“…Te concepts of supervisor knowledge sharing behavior and absorptive capacity have gained high momentum recently in knowledge management literature [15]. Several studies examined their role in shaping innovation and employees' performance at diferent contexts like tourism [26], information technology agencies [21], public services settings [27], and petroleum companies [8]. Meanwhile, opinions of respected nursing authorities give consensus that supervisor knowledge sharing behavior and organizational absorptive capacity are important factors to build creativity among nurses [28].…”
Section: Signifcance Of the Study And Research Gapmentioning
confidence: 99%
“…An effective MGS encourages employees to think further and look at the various organizational challenges from different angles, establishing a conducive environment where innovative ideas are properly recognized and rewarded (Matzler et al, 2008;Sharma et al, 2021). A better MGS helps to establish a knowledge-incentive environment that supports employees to improve their skillsets and acquire information which could eventually lead their organizations to facilitate the changes and motivate everyone to adopt new technology to achieve better innovation capability (de Moura et al, 2021;Fulgence et al, 2022). Small and medium businesses can use their MGS to integrate their human and organizational resources so that it is difficult for other market competitors to imitate (Wright et al, 2001).…”
Section: Managerial Style Mgs Helps An Organization To Achieve Value ...mentioning
confidence: 99%
“…Thus, small and medium businesses need to develop an effective MGS along with proper resource planning to become more compatible with adopting modern new technologies (Gobble, 2018; Bhattacharjee et al , 2021). Studies have suggested that by changing the MGS and making it more dynamic along with adopting new technologies, organizations can improve their innovative capabilities (Sheshadri, 2015; de Moura and Saroli, 2021; Fulgence et al , 2022; Thrassou et al , 2022).…”
Section: Background Studiesmentioning
confidence: 99%
See 1 more Smart Citation